Crack evolution and energy conversion characteristics of coal under acid corrosion conditions - Wenmei Han; Xiang Zheng; Zhihao Li; Qi Yuan (Scientific Reports)
Abstract In the process of coal mining with complex hydrological conditions, underground coal seams are often subjected to corrosion by acidic water, and acidic water–rock chemical interactions can significantly affect the mechanical properties of coal rocks, posing challenges for mine tunnel support and coal seam stability. This study investigates the effects of acidic solution exposure, specifically varying pH levels, on the mechanical and structural properties of coal samples. Static Brazilian splitting tests were conducted to determine the tensile mechanical properties of the treated coal samples. Additionally, the Particle Flow Code (PFC) was utilized to examine the evolution of microcracks, stress fields, and energy conversion characteristics within the coal samples. The results indicate that acidic solutions induce damage and softening of the coal structure, leading to a reduction in tensile strength and elastic modulus as acid corrosion intensifies. The primary mechanism of failure in the coal samples is attributed to the initiation, propagation, nucleation, and rapid consolidation of microcracks within stress concentration zones. A decrease in the area of stress concentration zones, increased stress unevenness, and reduced ultimate tensile strength in corroded coal samples lead to more complex crack propagation paths and lower macroscopic strength. Energy monitoring further reveals that acid-corroded coal has reduced resistance to damage and higher failure rates, highlighting the heightened vulnerability of acid-affected coal in structural applications.